Analisis Preferensi Konsumen terhadap Buah Jeruk Impor dan Buah Jeruk Lokal di Kota Denpasar, Bali - DWIASTARI, KADEK YUNNI; SUSRUSA, KETUT BUDI; ARTINI, NI WAYAN PUTU (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.8, No.3, Juli 2019, 2019)
Analysis of Consumer Preference on Imported Citrus Fruit and Local Citrus Fruit in Denpasar, Bali. This study aims to determine consumer preferences in buying citrus fruits in Denpasar City, and to find out the attributes of citrus fruits that are most dominantly chosen by consumers in purchasing decisions. The location of this research was conducted in Pasar Badung, Sanglah Market, Ketapian Market, and Pasar Kreneng which were determined purposively. Data collection method by distributing questionnaires to respondents. The population in this study are consumers of fruit buyers who have at least consumed and bought citrus fruits. The sample of this study amounted to 50 people conducted by accidental sampling method. The results in this study indicate respondents' preference in buying citrus fruits, as many as 35 (70%) people choose local oranges and 15 (30%) people choose imported oranges. In determining their preferences there are several indicators that influence respondents to choose the type of citrus fruit. Of the seven indicators namely taste, color, fruit size, price, personal taste, income level and availability continuity that most influence the respondents to choose the type of citrus that is preferred is the good fruit taste from respondents who choose local oranges and imported oranges. The fruit flavor indicator has the largest percentage of 71.42% for local oranges and 86.66% for imported oranges. The most dominant attribute chosen by consumers in buying local citrus fruits and imported oranges is the attribute of fruit flavor. Where the attributes of taste are the main consideration of respondents in buying citrus fruit compared to other attributes such as color, shape, cleanliness, size, price, texture, and freshness of fruit.